Association between spirituality and quality of life of women with breast cancer undergoing radiotherapy - Mayara Lindner Brandão; Thais Zilles Fritsch; Thayla Rafaella Pasa Toebe; Eliane Goldberg Rabin (SciELO, 2021)
ABSTRACT Objective: To verify whether there is an association between spirituality/religiosity and quality of life of women with breast cancer undergoing radiotherapy. Method: Cross-sectional, quantitative study performed between May and July 2019 in an Oncology Hospital of Porto Alegre state, Brazil. A sociodemographic questionnaire and the instruments EORTC-QLQ-C30 and WHOQOL-SRPB were applied. The data were verified through Shapiro-Wilk test, Pearson correlation coefficient, and Spearman. Results: The sample comprised 108 women with a mean age of 56, predominantly white, married, and with incomplete primary education. A positive correlation between "Overall quality of life score" with all facets of spirituality, as well as a negative correlation for the symptoms "Fatigue", "Insomnia", and "Diarrhea" with some aspects of spirituality, such as "Faith", were observed. Conclusion: The statistical significance of the correlation has positively associated spirituality/religiosity and quality of life in women with breast cancer undergoing radiotherapy. Understanding spirituality as a preponderant factor in quality of life contributes to positive nursing care interference, with individualized orientation and care to each woman.